Experimental Assessment of Moringa Oleifera as an Environmentally Friendly Inhibitor Solution for Gas Hydrate Control - Silas Oseme Okuma (Journal of Materials Engineering, Structures and Computation, 2025)
Research efforts have long been focused on developing low dose hydrate inhibitors (LDHIs) due to their accessibility, reduced quantity requirement, and cost-effectiveness. This study explores the potential of Moringa oleifera extract as an alternative LDHI, leveraging its established applications in the pharmaceutical and cosmetic industries. Utilizing a mini hydrate flow loop comprising 316 stainless steel pipes covered with polyvinyl chloride (PVC) mounted on a steel frame, hydrate formation conditions are simulated. Moringa Leaf Extract (MLE) concentrations of 0.02%, 0.04%, and 0.06% by water volume are compared against Methanol concentrations of 2%, 4%, and 6%. Performance evaluation entails analyzing pressure, temperature, inhibition efficiency, and pressure-time plots. Results indicate that 0.04wt% MLE surpasses all Methanol concentrations, exhibiting an inhibition efficiency of 60%, while the optimal Methanol concentration is found to be 2%, with an efficiency of 56.7%. MLE emerges as a promising alternative to traditional hydrate inhibitors, being readily available, environmentally friendly, and cost-effective.
Keywords: Moringa Oleifera; Hydrate inhibitor; Phytochemicals; flowloop; Hydrate formation